Pura Vida: Affect, Puerto Viejo, and Emergent Tourism Erotics - Maksymowicz, Kristofer (Téoros)

(untitled) (Université du Québec à Montréal, 2018)
Located approximately four hours southeast of San José on the Caribbean Coast of Costa Rica, Puerto Viejo de Talamanca is a burgeoning tourist town thoroughly characterized and “eroticized” in guidebook, anthropological, and ethnographic representations, as a place where “tourist women come to ‘hook up’ with local, Afro-Caribbean men.” Drawing on recent developments at the intersections of affect studies and the anthropologies of tourism, in this experimental paper, I seek to augment and accomplish a disruption of such representational and critical assessments, specifically, through a retooling of salient tourism studies concepts such as encounters and contact zones, toward a theoretical orientation that explores “eroticization” as an affectively charged, durative, and ongoing process of becoming. In doing so, I further experiment with ethnographic writing practices and conventions adequate to this task, thereby enacting a mimetic performance of affects toward an extension of their disruptive potentials. To that effect, I take up locally and touristically inflected notions of vortices, understood as seductive and relational affectively charged pulls that draw tourists and locals alike into new and ongoing infrastructures of difference, for better or for worse.